2017
DOI: 10.14814/phy2.13319
|View full text |Cite
|
Sign up to set email alerts
|

Increased FNDC5 is associated with insulin resistance in high fat-fed mice

Abstract: FNDC5/irisin, has recently been identified as a novel protein that stimulates the “browning” of white adipose by inducing thermogenesis via increased uncoupling protein 1 (UCP1). We tested the hypothesis that high fat diet‐induced prediabetic mice would exhibit increased FNDC5 and this effect would be attenuated by chronic exercise. C57BL/6 mice were randomized into three groups for the 4 week intervention: Standard diet (Std, n = 12), High fat diet (HF, n = 14), or High fat diet and free access to a running w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 37 publications
4
19
1
1
Order By: Relevance
“…Although some reports have shown significant increases in fasting serum glucose in rats subjected to long-term (5-10 months) HF diets (Chalkley et al, 2002;Choi et al, 2012), this index did not differ here, indicating that an HF diet for 3 months may not be sufficient to alter glucose homeostasis in pigs (Kim and Park, 2010;Azorín-Ortuño et al, 2012). Our result was consistent with previous studies in both swine and rat models that an HF diet leads to plasma insulin up-regulation (Guilford et al, 2017;Liu et al, 2017;Malbert et al, 2017;Yang et al, 2017), and possibly insulin resistance. The adipose-derived hormone leptin is considered to be an adiposity signal (Munzberg, 2010), and blood leptin levels are proportional to WAT stores (Gimeno and Klaman, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…Although some reports have shown significant increases in fasting serum glucose in rats subjected to long-term (5-10 months) HF diets (Chalkley et al, 2002;Choi et al, 2012), this index did not differ here, indicating that an HF diet for 3 months may not be sufficient to alter glucose homeostasis in pigs (Kim and Park, 2010;Azorín-Ortuño et al, 2012). Our result was consistent with previous studies in both swine and rat models that an HF diet leads to plasma insulin up-regulation (Guilford et al, 2017;Liu et al, 2017;Malbert et al, 2017;Yang et al, 2017), and possibly insulin resistance. The adipose-derived hormone leptin is considered to be an adiposity signal (Munzberg, 2010), and blood leptin levels are proportional to WAT stores (Gimeno and Klaman, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, high-dose melatonin supplementation (MEL50) significantly enhanced the circulating irisin level compared to the PC group. FNDC 5/irisin has recently been identified as a novel protein that can stimulate the browning of white fat by inducing thermogenesis through increasing UCP1 [ 35 ]. In the study, we found that melatonin could increase circulating irisin level, which binds to the surface of white adipocytes to induce the expression of UCP1 and trigger the transformation of white adipocytes into brown adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast with a previous study in mice on a 54% kcal fat diet for only 8 weeks (da Silva Franco et al, 2017 ). In terms of plasma glucose and insulin, most studies report a rise induced by HFD, even after only 4 weeks of feeding (Guilford et al, 2017 ), but others have found no change after 6 weeks (60% kcal of fat diet; Zhang et al, 2017 ). Our study used a diet with a lower percentage of kcal as fat (42%) and we cannot rule out changes occurring if feeding duration was increased beyond 12 weeks as both plasma insulin and glucose showed trends toward an increase in both HFD groups.…”
Section: Discussionmentioning
confidence: 99%